Bitumen stabilised ballast: a novel track-bed solution towards a more sustainable railway - D'Angelo, Giacomo (2018)
Ballasted track represents by far the most used infrastructure for railway transportation system, its main benefits being the relatively low construction costs, the maintainability, the relatively high damping capacity, noise absorption and high flexibility, the self-adjusting properties and high hydraulic conductivity. These are related to the structure of ballast layer as assembly as well as to particle properties. However, the unbound nature of ballast layer is also responsible for the reduction of geometric quality of the track, and therefore, its safety and ride comfort. The passage of trains causes cyclic movements of the unbound particles that result in permanent vertical and lateral deformations. For this track form, vertical settlement of granular layers and ballast particles degradation represent the major problems, affecting frequency of maintenance and track durability. In this context, reducing minor and major maintenance frequency while effectively using available resources by developing innovative technologies is a challenge for current and future railway research. After reviewing the most relevant existing solutions to improve ballasted track-bed behaviour and main factors affecting their performance, the aim of this research was to investigate the possibility of stabilising ballast with bitumen emulsion, as novel solution to slow down the loss in track quality associated with ballast settlement and particle degradation. In this regard, firstly the feasibility of the proposed alternative and main factors affecting its performance have been assessed through model-scale testing (small-scale Precision Unbound Material Analyser - PUMA). Results showed a good potential for this technology to reduce both the short-term and the long-term permanent deformation. It was also observed that bitumen stabilisation could modify mechanical properties due to the presence of a viscoelastic component (bitumen). The type of emulsion and its dosage played important roles in BSB properties: increasing the dosage of bitumen emulsion provided a better resistance to permanent deformation; increasing the viscosity of bitumen emulsion decreased the percentage of material lost, thereby providing improved stabilisation efficiency. Thus, depending on the field condition a specific bitumen emulsion could be designed to obtain the desired results in terms of BSB behaviour and stabilisation efficiency. At the same time, the use of harder bitumen for BSB seemed to improve the resistance to permanent deformation while polymer modification provided a more stable behaviour over time. Model-scale results provided important guidance on the influence of the factors analysed on the proposed technology. Nevertheless, to understand to what extent BSB could represent a solution to improve sustainability and performance of ballasted track-beds, findings had to be verified at full scale. Thus, full-scale box tests have been employed to assess how this technology could be effectively applied to existing ballasted tracks during maintenance operations and to investigate the practicability and maintainability of the presented technology. Results showed that bitumen stabilisation was more effective when applied at an early stage of ballast life (clean ballast), especially when coupled with tamping, providing a significant decrease to permanent deformation and to deformation rate (long-term behaviour). Nonetheless, in comparison with results obtained at model-scale, a slightly different behaviour of BSB in relation to unbound material was observed. Thus, with the aim of correlating previous model-scale PUMA and full-scale ballast box findings and evaluating long-term performance, full-scale PUMA testing was carried out. Results on clean ballast indicated that scale factor instead of the test type was the main factor controlling the effectiveness of Bitumen Stabilised Ballast (BSB) in terms of permanent deformation reduction. On the other hand, results obtained when using lower size aggregate confirmed that increasing the number of contact points increases also the influence of viscoelastic properties given by the bitumen, indicating that the use of different gradations combined with higher dosages (and types) of bitumen emulsions, could potentially modify full-scale track-bed mechanical properties. Key findings obtained from laboratory experiments, consistently showed evidence of the fact that bitumen stabilisation can reduce number of maintenance interventions due to geometry corrections and excessive particle degradation. In this regard, to estimate the environmental and economic impacts of BSB, a performance-based integrated model was developed to predict maintenance strategies of proposed technology in comparison to traditional ballast. This model, by combining the evolution of track irregularities with traffic and the level of contamination of ballast, allowed evaluation of the timing of corrective maintenance activities. Based on these, life-cycle environmental and economic costs of these alternatives have been carried out. Life Cycle Assessment (LCA) results showed that BSB is overall more sustainable than traditional ballasted track, only when considering also its impact on major maintenance operations. Sensitivity analysis carried out showed that BSB advantages are generally higher when the tolerance on the track quality level increases and with heavy traffic lines. LCCA results showed that BSB can provide important savings with respect to traditional ballasted track-bed. Sensitivity analysis showed that BSB would be more profitable for important and congested lines rather than peripheral ones. The influence of carbon conversion factor on results is relatively low while decreasing the discount rate corresponds to higher savings provided by the BSB. Overall, both LCA and LCCA results showed that BSB could offer a more sustainable solution from a life cycle perspective than traditional ballasted track-bed.